Mid to Long-Term Outcomes of Low-Energy Selective Laser Trabeculoplasty for Primary Open Angle Glaucoma - Hinako Ohtani; Yuri Fujino; Keigo Takagi; Yuto Yoshida; Chisako Ida; Kana Murakami; Mizuki Koike; Masaki Tanito (Journal of Clinical Medicine, 2026)
Background/Objectives: To evaluate the mid- to long-term outcomes of selective laser trabeculoplasty (SLT) performed with lower energy (≤0.5 millijoules (mJ)) than conventional settings (0.6–1.2 mJ). Methods: This retrospective chart-review study included patients who underwent low-energy SLT (0.34 ± 0.06 mJ) at Shimane University Hospital from April 2018 onward. A total of 54 patients (99 eyes) were analyzed, with a mean follow-up period of 57.5 months and a maximum follow-up period of 114 months. Treatment failure was defined using two criteria: an increase in the number of medications or the addition of incisional glaucoma surgery, and the addition of incisional glaucoma surgery. Kaplan–Meier survival analyses and multivariate Cox proportional hazards models were performed to evaluate long-term outcomes and prognostic factors. Results: During the follow-up period, 54 eyes underwent a single SLT treatment. A total of 37 eyes underwent two SLT treatments, and 8 eyes underwent three treatments. Mean intraocular pressure (IOP) significantly decreased from 16.7 mmHg at baseline to 15.1, 14.4, and 13.9 mmHg at 12, 36, and 60 months, respectively (mixed-effects model, p < 0.0001). Medication scores were 2.2, 2.3, 2.1, and 2.8 at baseline, 12, 36, and 60 months, respectively (p = 0.0006). Success rates at 12, 36, and 60 months were 72%, 37%, and 26% by Definition 1, and 90%, 69%, and 61% by Definition 2. At 36 months, success rates stratified by baseline medication score (0, 1–2, and ≥3) were 11%, 50%, and 38% for Definition 1 (p = 0.0002), and 83%, 75%, and 58% for Definition 2 (p = 0.02). Under Definition 1, more than 90% of eyes in the medication-free group required additional medications or surgery within 5 years. Under Definition 2, 60% of eyes with a preoperative medication score of ≥3 required surgeries within 5 years. Conclusions: Performing low-energy SLT in patients using approximately one medication can delay the need for additional therapy or surgery while maintaining IOP reduction over the observation period.